Androgen receptor in the Mongolian gerbil ventral prostate: Evaluation during different phases of postnatal development and following androgen blockage - Cordeiro, Renato S.; Scarano, Wellerson R.; Campos, Silvana G. P. [UNESP]; Santos, Fernanda C. A. [UNESP]; Vilamaior, Patricia S. L.; Goes, Rejane M. [UNESP]; Taboga, Sebastiao R. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The normal growth, differentiation and maintenance of the morphofunctional integrity of the prostate gland are dependent on the interaction of constant levels of androgens with their receptors. The need to study the responses to hormones under several conditions and the effect of their blockage is due to the fact that the human prostate is the site of a great number of age-related diseases, and the ones with a major medical importance are prostate cancer (Cap) and benign prostatic hyperplasia (BPH), which can both be treated with androgen suppression. Seventy-five male gerbils were divided, randomly, into 3 groups of 25 animals each, where each group corresponded to one phase of postnatal development. In each phase, it was possible to morphologically and stereologically analyze the compartments of prostatic ventral lobe, as well as to immunohistochemically analyze the degree of expression of androgen receptors (ARs) after the androgen blockage therapies. In addition, it was possible to establish the hormonal dosage of serum testosterone levels given the comparative approach of the expression of androgen receptors. There is a pattern of AR distribution in the prostatic ventral lobe throughout postnatal development, in which the younger the animal is the higher, the interaction of circulating androgens that stimulate the AR expression in both the epithelial and stromal compartments. The androgen blockage therapies decreased AR expression in the prostatic compartments, but the androgen reposition after these blockages was not sufficient to recover the glandular structure or stimulate the AR expression up to normal physiological conditions. Both the regulation and distribution of androgen receptors along the gerbil prostatic tissues are complex mechanisms that are likely to be genetically regulated by androgens prenatally or by other factors that are still unknown. This rodent species seems to be a valuable model in the attempt to improve the understanding of the morphophysiological and pathological behavior of this important gland in humans throughout aging and to stimulate new therapeutic ideas to fight prostate cancer. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Androgen receptor; Ventral prostate; Castration; Testosterone